Incidental Identification of Plasmodium vivax During Routine Complete Blood Count Analysis Using the UniCel DxH 800 - Shin, Soyoung; Park, Sun Hee; Park, Joonhong (Annals of laboratory medicine, 2018)
Dear Editor, A complete blood count (CBC) is one of the most frequently requested diagnostic tests in medical laboratories. This test is indicated, among others, for febrile patients who may be infected with malaria [1]. Currently available automated hematology analyzers are not designed to detect malaria-related signals. The incorporation of a ‘malaria flag’ into modern analyzers would allow for the development of an automated and adjuvant diagnostic tool for febrile patients who may have malaria, especially for patients with low pre-test expectation of the disease in non-endemic regions. KCI Citation Count: 0